2011
DOI: 10.3892/or.2011.1276
|View full text |Cite
|
Sign up to set email alerts
|

β-elemene inhibits proliferation of human glioblastoma cells through the activation of glia maturation factor β and induces sensitization to cisplatin

Abstract: Abstract. β-elemene, a natural drug extracted from Curcuma wenyujin, strongly inhibits glioblastoma growth. However, the mechanism of β-elemene antitumor action remains unclear. glia maturation factor β (gMFβ) regulates cellular growth, fission, differentiation and apoptosis. It has been reported that overexpression of GMFβ inhibits the growth of glioblastoma cells and decreases tumor volume. to illustrate the role of gMFβ in the anti-proliferative effect of β-elemene in glioblastoma, U87 cells were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Moreover, it has also been demonstrated that β -caryophyllene and caryophyllene oxide were also reported to induce apoptosis in tumor cells and exert analgesic, anti-inflammatory, antibacterial, antifungal, and sedative activities [21, 22]. Furthermore, β -elemene and spathulenol were reported as having anticancer activities on human glioblastoma and on MCF7 cancer cell lines [2325]. Interestingly, no cytotoxic effect of A. citriodora essential oil studied here was observed on Human peripheral blood mononuclear cells (PBMCs).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been demonstrated that β -caryophyllene and caryophyllene oxide were also reported to induce apoptosis in tumor cells and exert analgesic, anti-inflammatory, antibacterial, antifungal, and sedative activities [21, 22]. Furthermore, β -elemene and spathulenol were reported as having anticancer activities on human glioblastoma and on MCF7 cancer cell lines [2325]. Interestingly, no cytotoxic effect of A. citriodora essential oil studied here was observed on Human peripheral blood mononuclear cells (PBMCs).…”
Section: Discussionmentioning
confidence: 99%
“…In C6 and U251 glioblastoma cells, elemene treatment resulted in p38 MAPK phosphorylation and cell-cycle arrest at the G0/G1 phase (Yao et al, 2008a,b). Activation of Glia maturation factor β mediates the antitumor effect of elemene in glioblastoma cell line U87 and this can increase the sensitivity of cancer cells to cisplatin (Zhu et al, 2011a). Therefore, the antiglioblastoma effect of elemene is mediated through the cell cycle arrest at G0/G1 phase, leading to MAPK phosphorylation.…”
Section: Elemene Mechanism Of Action Against Cancer Cells Of Multiplementioning
confidence: 99%
“…In the People’s Republic of China, ELE has been used to treat glioma clinically 9,18. Recent in vitro investigations have also shown that when treating GMB, ELE was not only an antitumor agent but also a chemo- and radiosensitizer 1114. In this clinical study, we focused on the use of ELE in GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its small molecular weight and lipid solubility, ELE can penetrate the blood–brain barrier4 and has been used to treat glioma 9. Recently, several in vitro studies showed that ELE treatment inhibited GBM cell proliferation,10,11 promoted differentiation,12 induced apoptosis,13 and chemo- and radiosensitized GBM cells 11,12,14. All these findings indicated the potential survival benefit of ELE in treating GBM.…”
Section: Introductionmentioning
confidence: 94%